Validation of proxy-reported EQ-5D-Y-3L in younger children with spinal muscular atrophy: age-related differences in performance - Chenxi Yang; Janine Verstraete; Richard Huan Xu; Dong Dong (The European Journal of Health Economics, 2026)
Abstract Objectives This study aimed to examine the psychometric performance of the proxy-reported EQ-5D-Y-3L (Y-3L) for children living with spinal muscular atrophy (SMA) aged between 5 and 12 years, with a particular focus on examining whether its properties differ across three age groups. Methods Patients were recruited through a nation-wide patient advocacy association in China. Parents of eligible patients were invited to complete a web-based survey. Proxy-reported cross-sectional data from children aged 5–12 years were included in the analysis and categorized into three age groups: 5–6, 7–8, and 9–12 years. Convergent validity, known-groups validity, and the explanatory power of the Y-3L were assessed across the three age groups as well as in the overall sample. Results The Y-3L showed strong ceiling effects for “pain/discomfort” and “feeling worried, sad, or unhappy,” and floor effects in the three physical dimensions. Ceiling effects generally decreased with age for “pain/discomfort” and “feeling worried, sad, or unhappy.” Level sum scores and index values correlated moderately to strongly with other measures. Four dimensions correlated well with comparator scales, but “doing usual activities” showed weaker links. Known-groups validity was highest for Y-3L, with clear age differences. Y-3L dimensions explained less EQ VAS variance with age, while emotional problems were more influential in 5–6-year-olds. Conclusion The Y-3L is a valid instrument for assessing health-related quality of life in SMA children aged between 5 and 12 years, with better psychometric properties observed in older children aged over 7 years.